Textbook for Small Multiethnics Islands In Indonesia - Ramli, Murni; Rochwulaningsih, Yety; Sulistiyono, Singgih Tri; Masruroh, Nailil (Proceeding of International Conference on Teacher Training and Education, 2016)
More than five ethnics are living in harmony in five inhabited islands of Karimunjawa, the west southern archipelago of Java Island. Karimunjawa has uniqueness of its society and natural resources. One of the crucial problems of education in Karimunjawa is the lack of reading resources or textbooks, which are contextually promoting the localities. Commonly used textbooks describe facts, culture, or society of common Indonesia, but locality, ethnicity-based indigenous knowledge, nature, environment, fishermen life, indigenous technology, and ethnicâs harmonious life had not been mentioned yet in those textbooks. This research explored and identified what should students of multicultural society learn about their diversity nature and society. The textbooks are suitable for ES grade 4, 5, and 6. The draft of the textbooks had been validated as quite good by three experts, and need to be revised on content and to be more inquiry based, and suitable for ES students.